Petrología y geoquímica del magmatismo Jurásico-Cretácico vinculado a las mineralizaciones de Fe-Cu del cerro Pepita, SO del Chubut - Lanfranchini, Mabel Elena (2006)
Fe-Gu skarn arel hydrothermal deposils, al the Pepita Hill ('Al Chubut Pruvince), are relató to Jurassic-Cretaccous magmatism. Detailed petrographic studies arel Mole rock cieocliernical analyses perforrned on andesite fk-D.vs (Lago La Plata Fm) arad rhyolític-dacitic dikesand subvolcanic bodies (ElGato Fm) allowed tocharacterize the meta-aluminous to weakly per-aluminous, tholeiite-calc-alkaline signature, associated to a magrnaticarcsetting. The iron source of the El Abuelo ore deposit is possiblyrelated to the tholeiitic affinity of rocks from Lago La Plata Forrnation.